2007
DOI: 10.1530/eje.1.02309
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and hip structural analysis in type 1 diabetic men

Abstract: Objective: The risk of non-vertebral fractures is increased in men with type 1 diabetes (DM1) but studies have shown only moderately decreased or normal bone mineral density (BMD) in these patients. No previous studies have evaluated hip strength and geometry indices in DM1 patients. This study was therefore designed to characterize associations between BMD, dual X-ray absorptiometry (DXA)-based hip strength indices, metabolic control, and DM1chronic complications. Design and methods: The study was performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 31 publications
(34 reference statements)
1
19
0
3
Order By: Relevance
“…Some studies, however, documented the presence of osteopenia at diagnosis of diabetes (35). As depicted in Table 1, BMD correlated poorly with glycaemic control in most (29,33,34,35,36,37), but not all (28,31,32), studies. However many studies reported an association between the presence of microvascular complications of diabetes and the presence and/or progression of a decreased BMD (27,28,38,40,42,50).…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies, however, documented the presence of osteopenia at diagnosis of diabetes (35). As depicted in Table 1, BMD correlated poorly with glycaemic control in most (29,33,34,35,36,37), but not all (28,31,32), studies. However many studies reported an association between the presence of microvascular complications of diabetes and the presence and/or progression of a decreased BMD (27,28,38,40,42,50).…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
“…Although the decreased BMD reported in subjects with T1DM (27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,50,58) may largely explain the higher fracture risk observed in these patients (17,18,19,20,21,22,26), alterations in bone quality, as described below, may also contribute and actually confer its specific nature to diabetic bone disease.…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Встановлено, що у чоловіків із соматичною патологією за наявності клінічних і лабораторних ознак андрогенного дефіциту поширеність остеопорозу є значно вищою, ніж у чоловіків з їх відсутністю. За дефіциту андрогенів низька МЩКТ виявляється у понад 87% випадків, за його відсутності -приблизно у 12% [43].Незалежно від нозологічних форм андро-генного дефіциту та рівня порушення гормо-нального гомеостазу клінічні прояви дефіциту кісткової маси є однотипними, що дозволяє використовувати стандартну інструментальну оцінку щільності кістки.Показаннями для проведення оцінки МЩКТ у чоловіків є [34]:-вік 70 років і більше; -вік до 70 років і наявність чинників ризику переломів (попередні переломи у віці до 40 років, надто хребців; системна глюкокортикоїдна терапія понад 3 місяці; захворювання, що спричиняють втрату кісткової маси; родинний анамнез остеопо-розу; зловживання алкоголем, паління тютюну; низький (<20 кг/м 2 ) індекс маси тіла; застосування антиандрогенної терапії); -будь-який вік за наявності в анамнезі переломів низького рівня травми; -вживання лікарських засобів, що впливають на кістковий метаболізм; -захворювання, що впливають на кістковий метаболізм.За даними низки досліджень, у пацієнтів із ЦД 1-го типу виявляються нижчі показники МЩКТ у ділянці стегна та поперековому відділі хребта порівняно з контролем [26][27][28]. Метаболічні проце-си у кістковій тканині залежать від структури кістки та відбуваються у трабекулярній кістковій тканині активніше, ніж у кортикальній.…”
unclassified
“…Неоднозначними є також резуль-тати досліджень впливу статі на частоту розвитку цього ускладнення. Одні автори вважають, що роз-виток кісткових змін за ЦД не залежить від цього чинника, інші дотримують протилежну точку зору [13,20,26,28]. Вважається, що значний вплив на кістковий метаболізм справляють гормональний дисбаланс і дефіцит інсуліну, судинні та неврологічні порушення, недостатність остеогенезу за ЦД 1-го типу.…”
unclassified